ACTIVITIES OF OXIDATIVE ENZYMES OF BOTH HEALTHY AND FUNGI-INFECTED CASSAVA ROOTS - SALAMI, ABIODUN OLUSOLA; AKINTOKUN, ADERONKE KOFOWOROLA (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2020)
Production of oxidative enzymes of post-harvested cultivars of cassava was investigated in the laboratory when inoculated with four pathogenic fungi causing rot disease. Three cultivars of cassava namely Oko-Iyawo; Odongbo (local cultivars); and TMS 4(2) 1425 (a hybrid cultivar) and four pathogenic organisms (Fusarium pallidoroseum; Macrophomina phaseolina; Lasiodiplodia theobromae; and Rhizopus stolonifer) were used in this study. Results of this study revealed that Polyphenol oxidase (PPO) and Peroxidase activities increased from day 1 (one) up to day 6 (six) or 8 (eight) in both healthy and infected cultivars. Regression analysis revealed a measure of rate of change in infection caused by different test organisms as induced by storage days. Mycelia dry weights of the test pathogens decreased with decreasing incubation periods. Enzyme production and activities of test pathogens in the utilization of different carbohydrate sources varied with the different carbohydrate sources and the test pathogens. Generally, this study showed that post-harvest rot disease of cassava roots is widely distributed and that presence of the oxidative enzymes within the harvested roots could not totally impose resistance against ingress of the pathogens. They can only create immunity against these pathogens for a short time; this was according to the regression analysis, which shows that the shelf-lives of the roots depend largely on the number of storage days and the varieties of the cassava roots after harvest. Thus, measures to increase the shelf life of harvested cassava roots should be taken into consideration.